A scoping review of educational methods to optimize parental self-efficacy and health literacy in improving the quality of life among children with thalassemia: Evidence from Asian studies - Yuyun Sarinengsih; Fania Putri Alya; Zaliha Harun; Gunavathy (Physical Therapy Journal of Indonesia, 2025)
Background: The success of parents in managing thalassemia in children is influenced by several important aspects, including self-efficacy and health literacy. Educational programs specifically designed for parents and children with thalassemia have been shown to improve the quality of life of children significantly. This scoping review aimed to identify and map family-centered educational interventions that enhanced parental self-efficacy and health literacy to improve the quality of life for children with thalassemia. Methods: This research employs a scoping review method, following the preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) guidelines. A literature search was conducted across four databases: EBSCO, PubMed, Scopus, and Taylor & Francis, as well as the search engine Google Scholar. Inclusion criteria included full-text articles in English, primary studies discussing educational interventions related to self-efficacy and health literacy, and studies with a quality score ≥70% based on the Joanna Briggs Institute (JBI) assessment. Exclusion criteria consisted of secondary research such as literature reviews and editorials, as well as studies with a JBI score below 70%. The study selection strategy used the PICO (population, intervention, comparison, and outcome) approach. Total of 17 articles were finally included in the analysis. Results: A total of 17 articles were found and included in the study. There are two types of interventions, conventional and digital-based educations. The media used in conventional education include booklets, pamphlets, posters, and PowerPoint presentations, along with methods such as lectures, group discussions, and training sessions. In addition, digital-based education in this study was a smartphone app and mobile learning. Conclusion: Conventional and digital-based educations have the potential to be effective methods in optimizing parental self-efficacy, health literacy, and knowledge, which can improve the quality of life for children with thalassemia.